Gingival Hypertrophy in Acute Promyelocytic Leukemia – A Rare Clinical Encounter - Arpit Shastri; Anurag Rohatgi; Shailaja Shukla; Roopali Dahiya; Aman Panchal; Divita Rohatgi (Indian Journal of Medical Specialities)
Acute promyelocytic leukemia (APL) is a subtype of acute myeloid leukemia (AML), a cancer of the white blood cells. Its common manifestations are fatigue, fever, coagulopathy, anorexia, and pancytopenia. Oral manifestations are identified in huge majority of patients with AML of which gingival hypertrophy is more specific to acute monocytic (M5) and acute myelomonocytic (M4) subtypes of AML. Very rarely, gingival hypertrophy may be encountered in patients with APL. Herein, we present a case of a young male who presented with gingival hypertrophy and was subsequently diagnosed with APL (M3).